The Family in Business - Seteroff, Sviatoslav Steve (Business Expert Press, 2011)
Ebook from IG Library ; Family-owned businesses (FOBs) are a breed unto themselves. Though they share many features in common with other business models, they possess unique traits that clearly differentiate them. Similarly, though consultation to FOBs is in many respects what other businesses experience when seeking assistance, those features that set FOB consultation apart are so distinctive that failure to honor and understand them can (and does) too often lead to disaster. The needs of those family members seeking consultation share a portrait in some ways similar to those in non-FOBs, but in a majority of situations are so distinctive and potentially explosive that disaster lurks on the edges, ready to appear if not respected. The audience for this book is both consultants to FOBs and family members who are looking for such assistance. Both require knowledge of each other's spheres of experience and perspective for effective consultation to occur - for the consultant, an awareness of family dynamics as intertwined with family business; for family members, a clarification of what can be expected and delivered. In addition to the interface between family dynamics and the family's business, we will explore the key tasks in FOB consultation: succession planning, selection of the successor, conflict resolution, defining the role of family members in the business, how to involve the management team in succession planning, determining what happens after succession and building a board of advisors.